The Relationship Between Hospitalization Anxiety and Sleep Quality in Pre-School Children (3-6 Years Old) - Tri Ratnaningsih; Peni, Tri; laili, siti indatul; Paramita, Prajna (Kirana Publisher (KNPub), 2023)
Factors that can affect the quality of sleep in pre-school-aged children are hospitalization anxiety, when experiencing anxiety, sympathetic nerves can increase so that it can interfere with the sleep process. The aim of this study was to analyze the relationship between hospitalization anxiety and sleep quality in pre-school aged children (3-6 years) at Mutiara Hati Gedeg Hospital, Mojokerto. The research method uses a correlation analytic design with a cross sectional study. The population of this research is pre-school age children as many as 40 respondents. The research sampling technique uses purposive sampling with the Lemeshow formula. The research was conducted on March 31, 2023 in the Children's Room of Mutiara Hati Hospital. The research instrument used the DASS questionnaire for anxiety and the PSQI questionnaire for sleep quality which had been modified by researchers with validity and reliability test results of 0.692 for hospitalization anxiety and 0.561 for sleep quality and Cronbach's Alpha 0.920 for hospitalization anxiety and 0.967 for sleep quality. The results of this study indicate that there is the most anxiety about hospitalization, namely moderate anxiety for 16 respondents (40%) and most pre-school age children experience moderate sleep quality as many as 18 respondents (45%). Spearman's rho statistical test results p value 0.002 <α 0.05, in the sense that there is a relationship between hospitalization anxiety and sleep quality. The benefits of accompanying parents, close family and siblings are that children are protected, feel comfortable and safe by providing positive support to children.